Value of the neutrophil-to-lymphocyte ratio in predicting left ventricular recovery in patients with peripartum cardiomyopathy - CAN GÜRKAN, ÖZLEM (SPRINGER WIEN, 2017)
The aim of this study was to assess the value of the neutrophil-to-lymphocyte ratio (NLR) in predicting left ventricular (LV) recovery in patients with peripartum cardiomyopathy (PPCM). Patients with PPCM (n = 40), who were admitted to our tertiary reference hospital between 2007 and 2015 were retrospectively analyzed. All patients were followed-up for at least 12 months after the diagnosis. All patients had standard echocardiographic examination at baseline and the last follow-up visit. Recovery of LV function was defined as the presence of LV ejection fraction (EF) > 45%. Data on blood parameters were also collected at baseline. Univariate and multivariate analysis were used to assess the significant predictive variables for persistent LV systolic dysfunction. Of the patients 21 (52.5%) did not recover LV function at the last follow-up visit (nonrecovery group), while 19 of the patients (47.5%) exhibited LV recovery (recovery group). The LV EF and fractional shortening (FS) were significantly lower in the nonrecovery group. The baseline LV end-diastolic diameter, LV end-systolic diameter (LVESD) and systolic pulmonary arterial pressure were significantly increased in the nonrecovery group. The NLR, CaEuroreactive protein and troponin levels were significantly higher in the nonrecovery group. In multivariate logistic regression analysis only NLR and LVESD were identified as independent predictors of persistent LV systolic dysfunction in patients with PPCM (p = 0.020 and p = 0.009 respectively). Elevated NLR and increased LVESD were independent prognostic factors in predicting persistent LV dysfunction in patients with PPCM. The NLR might assist in identifying high risk patients with PPCM.
Keywords: Peripartum cardiomyopathy; Left ventricular recovery; Neutrophil to lymphocyte ratio; HEART-FAILURE ASSOCIATION; INFLAMMATORY MARKERS; EUROPEAN-SOCIETY; PROGNOSTIC VALUE; DYSFUNCTION; MANAGEMENT; MORTALITY